Transcriptome analysis reveals the protection mechanism of proanthocyanidins for Saccharomyces cerevisiae during wine fermentation - Li, Jingyuan (Sci Rep, 2020)
Grape-derived proanthocyanidins could act as a protector against various environmental stresses for Saccharomyces cerevisiae during wine fermentation, resulting in the increased physiological activity, fermentation efficiency and improved wine quality. In order to explore the possible protection mechanism of proanthocyanidins globally, RNA-seq analysis for wine yeast AWRI R2 cultivated with 0 g/L (group A), 0.1 g/L (group B), 1.0 g/L (group C) proanthocyanidins were applied in this study. Differentially expressed genes were enriched into six metabolic pathways including vitamin B(6), thiamine, amino acids, aminoacyl-tRNA, carbohydrate and steroid based on KEGG enrichment analysis. Four key genes (SNZ2, THI6, THI21 and THI80), participated in the biosynthesis of vitamin B(6) and thiamine, were up-regulated significantly in proanthocyanidins treated yeast cells and the gene expression levels were verified by RT-qPCR. Yeast cells supplemented with proanthocyanidins performed increased intracellular levels of vitamin B(6) and thiamine and higher cell viability compared to the control group. In addition, the composition of intracellular fatty acids showed an obvious alternation in proanthocyanidins-treated yeast cells, in which the UFAs content increased whereas the SFA content decreased. In general, we provided an indirect protection effect of proanthocyanidins on the yeast cells to alleviate environmental stresses during wine fermentation.